2020
DOI: 10.3390/en13010237
|View full text |Cite
|
Sign up to set email alerts
|

How Climate Trends Impact on the Thermal Performance of a Typical Residential Building in Madrid

Abstract: Based on the European energy directives, the building sector has to provide comfortable levels for occupants with minimum energy consumption as well as to reduce greenhouse gas emissions. This paper aims to compare the impact of climate change on the energy performance of residential buildings in order to derive potential design strategies. Different climate file inputs of Madrid have been used to quantify comparatively the thermal needs of two reference residential buildings located in this city. One of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…As a part of the work, 13 prediction methods were proposed, four of them were discussed more precisely. To review the usage of the methods in more detail, in addition to those discussed, the following were also examined: ARIMA/SARIMAX, decision trees (Soutullo et al, 2020) 3.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of the work, 13 prediction methods were proposed, four of them were discussed more precisely. To review the usage of the methods in more detail, in addition to those discussed, the following were also examined: ARIMA/SARIMAX, decision trees (Soutullo et al, 2020) 3.…”
Section: Discussionmentioning
confidence: 99%
“…E-OBS also allows grid box average comparisons with the results of Regional Climate Models for validation purposes [25][26][27]. These datasets were used in various urban climatology studies relying on observations addressing the challenges of climate change in European cities, e.g., assessment of the impact of climate change on thermal performance of residential buildings [28]; and change in extreme heat/cold stress [29][30][31].…”
Section: In Situ Meteorological Datamentioning
confidence: 99%
“…Unsurprisingly, a drastic rise in cooling energy use and a moderate decrease in heating energy use is predicted [14][15][16]. Recently, in the study of Soutullo et al [17], for two reference buildings in Madrid, the annual heating and cooling requirements were shown to be around 22% lower and higher, respectively, just by considering the effect of climate change in the last decade. In addition, many studies revealed that this trend may happen even in energy efficient dwellings.…”
Section: Introductionmentioning
confidence: 99%